2021
DOI: 10.5171/2021.676983
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Housing Affordability of Homebuyers in Perak: Measuring Transport Expenditure

Abstract: Increasing housing prices in Perak has made it difficult for homebuyers to own affordable housing. Housing affordability ensures that housing provided is affordable for every income group, especially the low and middle-income groups. It has brought the government and housing developers’ attention the issue of housing affordability by supplying public low-cost housing schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Regency. This finding is inconsistent with previous research which stated that accessibility relates to housing affordability [7], [11], [15]. More specifically, the study by Baharun et al (2021) demonstrated that access to shopping facilities, public transport, recreation, and education affects housing affordability [15].…”
Section: Tangerang Regencycontrasting
confidence: 79%
See 2 more Smart Citations
“…Regency. This finding is inconsistent with previous research which stated that accessibility relates to housing affordability [7], [11], [15]. More specifically, the study by Baharun et al (2021) demonstrated that access to shopping facilities, public transport, recreation, and education affects housing affordability [15].…”
Section: Tangerang Regencycontrasting
confidence: 79%
“…This difference suggests that distance still affects affordability, but proximity does not guarantee lower transportation costs. and housing affordability [7], [11], [15]. Accessibility itself represents the ease with which MBR families can reach various amenities such as shopping, education, recreation, and public transportation.…”
Section: Bekasi Regencymentioning
confidence: 99%
See 1 more Smart Citation